Modelos de Churn de clientes em plano de saúde - Mendes, Vinícius de Paula (2008)
Nowadays, the drives on the market show that is more profitable for the companies to invest in relationships with customers, decreasing retention rates than choose to add new features to their portfolio. By knowing the risk associated with shutdown, the companies can direct marketing strategies to retain customers in areas of higher probability of evasion. Bringing up practices of relationship, they can ptimize the results of their marketing efforts by focusing on correct solutions. The purpose of this study is to develop a statistical model to link transactional and demographic information with the probability of unsubscribing. Additionally, we will determine the profile of customers with greater risk of unsubscribing in health plans. On this basis, the marketing managers become able to cener efforts on the retention of the most valuable customers, maximizing the results for the corporation and the satisfaction of the customers. Besides, intending to establish strategic profiles of customers, it will be offered an analysis using PSM, to compare customers with similar probabilities. Finally, some suggestions of directed actions to the company health plan administrator and of future researches are presented.